Anticipatory action planning for stepping onto competing potential targets - Watanabe, Ryo; Higuchi, Takahiro (Frontiers in Human Neuroscience, 2022)
The brain plans an anticipatory action for performing tasks successfully and effortlessly even if there are multiple possible options. There is increasing evidence that, when multiple actions are possible, the brain considers two factors when planning an anticipatory action—the probabilistic value and the action cost for each potential action. When the action involves maintaining upright balance, such as standing, stepping, or walking, the action cost for maintaining postural stability could be considered dominantly. We addressed this issue by using a “go-before-you-know” task to step onto a target on the floor. In this task, two potential targets were located on the medial or lateral side of the stepping foot, and the true target was cued only after participants shifted their loads to leave that foot. Participants initiated their stepping actions without knowing which of the potential targets would be the true one. The results showed that, for the majority of participants, lateral displacements of the center of pressure (COP) with two potential targets were similar to those when a single target exists on the individual’s medial side. Given that mediolateral postural stability became more destabilized with stepping onto the medial target than stepping onto the lateral target, they were likely to plan their mediolateral components of the postural adjustments for the worst-case scenario (i.e., falling). Additionally, posterior COP movements with two potential targets became smaller than those with a single target, suggesting an effort to create extra time to determine the true target and to adjust the swing foot. Based on these findings, we concluded that action costs for maintaining postural stability were considered dominantly for planning an anticipatory action to accomplish a stepping task successfully while ensuring upright balance.